PWE-043 Burden of Clostridium difficile Infection on hospitalization and its impact on specific Major Diagnostic Categories. (June 2019) - Caroli, Diego; Saia, Mario; Rosa-Rizzotto, Erik; Pilerci, Claudio; Lazzari, Franca De
Abstract : Introduction: Clostridium difficile infection (CDI) has emerged as a major healthcare-associated infection, with an important and constant increase in CDI hospitalization and mortality rates. Methods: To describe the epidemiology of CDI hospitalization in Veneto Region, a retrospective analysis based on the anonymous regional database was carried out including all discharges of the period 200–016 of population over 65 years of age with a code for CDI (008.45) as principal or secondary diagnosis. Data were stratified by Major Diagnostic Categories (MDC), which are formed by dividing all ICD-9-CM diagnoses into 25 mutually exclusive diagnosis areas, to evaluate the in-hospital mortality risk attributable to CDI of each MDC. Results: 6 640 discharges with CDI in patients over 65 years of age were tracked, with an overall lenght of stay (LOS) of 25.6±22, 7 days. Hospitalization distribution by gender showed a prevalence of females (63.2%) characterized by a higher mean age (80.2±14.6Vs. 75.6±16.4 yrs;p<0.001). The rate of CDI diagnoses per 100000 overall admissions increased steeply with age, and reached a peak of 222.4 every 100 000 discharges among the very elderly (> 85years). In the frame of over 65 years patients the age class distribution showed a higher risk in 7–4 (OR:1.62;p<0.001) and an almost double in >85 years (OR:2.1;p<0.001) respect to 6–4 age class. Over 65 years of age patients admission with CDI diagnosis represent 2.1‰ of overall ordinary admission and cause to the LOS excess of 15.7 days and represent the 5.4‰ of overall hospitalization days. Also in-hospital mortality rate showed an excess risk attributable to CDI (OR:1.91;p<0.001). As expected the MDC with most discharges of CDI was n.6 "Digestive"(36%) followed by 4 "Respiratory" (17%). The higher excess of in-hospital mortality risk was a prerogative of n. 8 "Musculoskeletal"(OR:5.55;p<0.001) followed by 11"Kidney And Urinary Tract" (OR:3.6;p<0.001) and 5 "Circulatory"(OR:2.35; p<0.001). Otherwise the presence of CDI showed a slight excess risk in MDC n.6 "Digestive"(OR:1.03;p<0.05), 18"Infectious and Parasitic"(OR:1.05;p<0.001) and 4 "Respiratory"(OR:1.01;p<0.001). Conclusion: In the observation period the standard hospitalization rate for CDI was almost doubled and standard of mortality rate even increased sixfold, with an increase in their frequency, as well as in their severity and in the additional days of hospitalization. Moreover the stratification of CDI by MDC showed a serious scenary in patients affected by musculoskeletal, kidney and circulatory diseases with an excess of in-hospital mortality risk associated to CDI.